Stay safe! Safety precautions for walking on a conventional treadmill in VR - Birnstiel, Sandra; Oberdörfer, Sebastian; Latoschik, Marc Erich (Proceedings of the 2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops, 2022)
Conventional treadmills are used in virtual reality (VR) applications, such as for rehabilitation training or gait studies. However, using the devices in VR poses risks of injury. Therefore, this study investigates safety precautions when using a conventional treadmill for a walking task. We designed a safety belt and displayed parts of the treadmill in VR. The safety belt was much appreciated by the participants and did not affect the walking behavior. However, the participants requested more visual cues in the user's field of view.<br
Keywords: Human computer interaction (HCI); HCI design and evaluation methods; Human-centered computing; Human-centered computing; Virtual Reality; Interaction paradigms